Pengembangan Pendidikan Islam Plural-Multikultural - Nur Efendi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Effort to develop plural-multicultural Islamic educations of great necessity to further expand and streamline the implementation of Islamic education that accommodates all forms of diversity and difference in the dynamic of life. Islamic educations essentially a multicultural education that put multiculturalisms one of the educational vision whose main characters are inclusive, egalitarian and humanist, but remained firm on spiritual values​​ and divinity based on al-Quran and as-Sunnah. Plural-multicultural Islamic education principle has clear basis, both in terms of prescriptive and empirical basis. Its principles has prominent characteristic, namely humanitarian and receive diversity. In addition, it has a great opportunity to continue to grow as it has a clear basis and is in accordance with the needs of today's society.